The Accessibility for Manitobans Act: Ambitions and Achievements in Antidiscrimination and Citizen Participation - Jacobs, Laverne; Costa, Britney De; Cino, Victoria (Canadian Journal of Disability Studies, 2016)
The Accessibility for Manitobans Act (AMA) was enacted in December, 2013. Manitoba is the second Canadian province to enact accessibility standards legislation. The first province was Ontario, which enacted the Ontarians with Disabilities Act in 2001, and, later, a more fortified and enforceable Accessibility for Ontarians with Disabilities Act, 2005. The AMA presents a strong set of philosophical and social goals. Its philosophical goals mark accessibility as a human right, and aim to improve the health, independence and well-being of persons with disabilities. The AMA’s social goals have the potential to make a positive impact on the development of equality law norms within the context of disability discrimination. Nevertheless, the AMA would be strengthened with a more robust and explicit appreciation of how disability discrimination issues are experienced. The Act should show a greater recognition of the relevance of embodied impairment to individuals with disabilities, and there should be more significant scope for the statute to address intersectionality within disability discrimination. These two challenges replicate the two principal critiques of the social model of disability –the model of disability on which the AMA is based. Finally, for the legislation to be successful, issues of compliance and enforcement that require positive uses of discretion on the part of the civil service should be addressed early on. The findings of this article may be useful for the implementation of the AMA and for the design of future accessibility legislation in Canada and elsewhere.
Keywords: Laverne Jacobs